CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

If a=cosα+isinα, b=cosβ+isinβ,

c=cosγ+isinγ and bc+ca+ab=1,Then

cos(β-γ)+cos(γ-α)+cos(α-β) is equal to


  1. 3/2

  2. -3/2

  3. 0

  4. 1


Solution

The correct option is D

1


bc=cosβ+isinβcosγ+isinγ×cosγisinγcosγisinγ

bc=cos(βγ)+isin(βγ).....(i)

Similarly, ca=cos(γα)+isin(γα).......(ii)

And ab=cos(αβ)+isin(αβ).......(ii)

Equating real and imaginary parts,

cos(βγ)+cos(γα)+cos(αβ)=1

flag
 Suggest corrections
thumbs-up
 
0 Upvotes


Similar questions
View More...



footer-image